Pengaruh Organizational Justice dan Team Work Terhadap Employee Engagement Pada Karyawan Koperasi Unit Desa (KUD) Pakis - Rofiatul Istiqomah; Pardiman Pardiman; Khalikussabir Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
Abstract      Employee engagement is something that can be one of the keys to organizational success. This study aims to determine the effect of organizational justice and team work on employee engagement on employees at Koperasi Unit Desa Pakis Malang. This type of research is explanatory research with a quantitative approach. The population in this study employees who had different positions in the Koperasi Unit Desa Pakis Malang with a total sample of 39 respondents. The sampling method using saturated sampling method. Data collection techniques in this study using a questionnaire. The data analysis used includes instrument test, classical assumption test multiple linier regression hypothesis test and determination coefficient  using SPSS. The result of this study indicate that organizational justice and team work have a simultaneous effect on employee engagement. The results of this study also indicated that there was a partial influence between organizational justice and team work on employee engagement.             Keywords : Organizational Justice, Team Work, Employee Engagement